Teachers’ characteristics, school factors as correlates of students achievement in basic science in secondary school in Oyo State (2025)
Several factors can influence learning process and the overall students’ performance but it seems that few studies had made attempt to investigate the influence of teachers and school factors on students’ achievement especially in a technological-driven world where Basic Science performance is low. The study investigated teachers’ characteristics and school factors as correlates of students’ achievement in Basic Science in Oyo State. The survey research was anchored on constructivism and theory of learning. Multi-stage sampling procedures were employed to select all the 33 Local Government Areas of Oyo State. Two schools each, 66 teachers and 1,980 students participated in the study. Three validated instruments used to gather information are: Teachers’ Characteristics and School Factors Questionnaire with r = 0.84, Teachers’ Observational Sheet with r = 0.87, and Basic Science Achievement Test with r =0.87. Data were analyzed using descriptive and inferential statistics at 0.05 level of significance. Significant relationship was found between teachers’ experience (r = 0.77, 0.003, P < .05), teachers’ subject mastery (r = 0.66, 0.019, P < .05), school location (r = 0.62, 0.031, P < .05), and students’ achievement. School facilities (β = 1.244; t = 2.487; p < 0.05) contributed significantly to the prediction. The variables jointly explained 82% of the variance observed in students’ achievement in Basic Science. There is a strong correlation of variables on students’ achievement. Teachers should improve on their subject mastery skill while enabling environment should be provided by the government.